2007
DOI: 10.1682/jrrd.2006.05.0055
|View full text |Cite
|
Sign up to set email alerts
|

Medical residents beliefs and concerns about using opioids to treat chronic cancer and noncancer pain: A pilot study

Abstract: Abstract-This study assessed and compared residents' beliefs and concerns about using opioids for treating pain in patients with cancer and noncancer low back pain (NLBP). Participants included 72 Internal Medicine and Medicine-Pediatrics residents who completed a survey questionnaire. Based on a scale of 0 = "No concern" to 10 = "Very concerned," residents expressed greater concern that treating NLBP with opioids, compared with cancer-related pain, causes addiction (6.01 vs 1.15), abuse (5.57 vs 1.39), and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[87][88][89] An abuse liability trial in opioid-experienced patients versus oral hydromorphone that was early in the clinical development of tapentadol reported a similar liking potential for oral tapentadol. In the United States and Europe, tapentadol is considered a scheduled substance 33,35 ; in the United States, the Food and Drug Administration has implemented a Risk Evaluation and Mitigation Strategy for controlled substances to improve prescribing practices and reduce drug diversion.…”
Section: Abuse and Diversionmentioning
confidence: 99%
“…[87][88][89] An abuse liability trial in opioid-experienced patients versus oral hydromorphone that was early in the clinical development of tapentadol reported a similar liking potential for oral tapentadol. In the United States and Europe, tapentadol is considered a scheduled substance 33,35 ; in the United States, the Food and Drug Administration has implemented a Risk Evaluation and Mitigation Strategy for controlled substances to improve prescribing practices and reduce drug diversion.…”
Section: Abuse and Diversionmentioning
confidence: 99%
“…For example, Kim et al . found that addiction was one of the four major barriers and Roth et al . found that physicians expressed more concern about addiction when opioids were prescribed for patients with noncancerous low‐back pain as compared to patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient pain management can also be related to prejudice against the use of opioids (ie, opiophobia), which mainly focuses on fear of addiction . Adequate pain management can also be impeded by a lack of knowledge of opioids (eg, their pharmacology) as well as by differences between definitions of dependence and addiction . In older persons, treatment of pain with opioids can also be complicated by side effects, which can be considerable due to different pharmacokinetics, such as changed absorption, distribution, and elimination .…”
Section: Introductionmentioning
confidence: 99%
“…Chaitowitz et al [7] reported deficiencies in the use of standardized pain scales, opioid equivalency tables, and over-estimation of the risk of addiction in a study of internal medicine residents. Roth et al [8] described barriers to effective treatment often reported by residents including a lack of skills for evaluation of abuse risk, limit setting, effective response to pain contract violations, patients who behave aggressively, and those requesting early prescription refills.…”
Section: Conceptual Backgroundmentioning
confidence: 99%